ANALISIS DETERMINAN PENGARUH MAKROEKONOMI TERHADAP RETURN SAHAM BANK BUKU 4 DI BURSA EFEK INDONESIA - Pardomuan Sihombing; Irwan Daud (Journal of Social Research, 2022)
This study aims to analyze the macroeconomics of Bank BUKU 4 returns. This study uses the Vector Error Correction Model (VECM) using monthly return data for Bank BUKU 4 shares as the assessment variable and monthly inflation data, BI 7-day reverse repo interest rate. exchange rates, exchange rates, money supply, gross domestic product, foreign exchange reserves, and fed funds interest rates, as independent, with a data time span from January 2016 to December 2020. The results show that in short-term inflation, GDP, and variable reserves foreign exchange varies. , and the fed funds rate does not affect stocks. The BI 7 day reverse repo rate and money supply variables have a significant positive effect, and the exchange rate has a significant negative effect on BUKU 4 bank stock returns. In long-term inflation, the BI 7 day reverse repo rate, money supply, GDP, foreign exchange reserves, and The Fed funds rate does not affect stock returns. While the exchange rate has a significant negative effect on stock returns of BUKU 4 banks.